Literature Review : Factors Influencing The Implementation Early Initiation of Breastfeeding in Mother’s Materials - Ariani, Dini; Septiani, Hani; Sunarni, Neli (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Initiation Early Breastfeeding has been proven to reduce neonatal mortality. The practice of initiating breastfeeding within the first hour of birth, known as Early Initiation of Breastfeeding (EIBF) benefits both the mothers and their children. It reduces mortality among infants through increased exclusive breastfeeding and associated mechanisms by allowing the infants to get the highly nutritious maternal colostrum that reduces the risk of microbial translocation, accelerates intestinal maturation and promotes resistance to infection. EIBF also reduces the risk of hypothermia and helps develop bonding between mother and baby through close physical contact. Method: The method used in writing this article is a review of the results study which related with factors influencing the implementation early initiation of breastfeeding in mother’s materials. Result: Five studies wich analyzed in literature reviews this form factors influencing the implementation early initiation of breastfeeding in mother’s materials. Conclusion: Many kinds of factors influencing the implementation early initiation of breastfeeding in mother’s materials. There are education, type of birth, knowledge, attitude, support from health workers, parity, family support, habits, midwife knowledge, midwife support, midwife training and skin-to-skin contact between mother and infant immediately after birth.